Event organizer application - Tai, Yik Teng (2018)
Nowadays, organizing an event is not an easy task as it needs alignment with everyone involved from planning till the event implementation. Also, hustle and bustle life of people nowadays and geographical distance have become main factors that contribute to poor communication on event especially during information passes down. This project studies on existing event organizer applications and develop a mobile application platform for event organizing. Rapid Application Development (RAD) methodology is being used in this project with Java programming language and code development in Android Studio environment. This developed application successfully integrated basic event organizer functions for event management and some special functions to ease the event planning, scheduling, and communication between people such as event note, chat, reminder, push notification and etc. All these functions help user to establish proper communication, have better understanding about event and reduce the risk of missing any information about event. This application can be further improved by developing in vary mobile platform and allow user to access it during offline mode in the future.